Freedom and Access to Housing: Three Conceptions - Skolnik, Terry (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
This article argues that our current understanding of the relationship between access to housing and liberty (or freedom) is limited. It contends that judicial decisions and existing legal theory are predominantly concerned with the connection between housing and the two conceptions of liberty famously advanced by Isaiah Berlin: positive liberty and negative liberty. The notion of positive freedom conceptualizes freedom as self-mastery, whereas negative liberty portrays freedom as non-interference. The central premise of this article is that the republican theory of freedom (or republicanism) provides new insight into the importance of access to housing in protecting liberty, most notably in contexts where the state regulates public property, such as in Canada and the United States. The republican theory of freedom defines liberty as non-domination, meaning the absence of others’ power to interfere with an individual’s life and actions. This article argues that we develop a more well-rounded grasp of the value of access to housing by understanding its role in protecting individuals against domination.This article concludes by setting out the four concrete ways that housing reduces domination and safeguards individual freedom in contexts where the state regulates public property. By combining the respective insights of positive liberty, negative liberty, and republican liberty, this article ultimately provides a more robust understanding of the importance of housing in protecting freedom.